Efeito do modo de ativação da polimerização e envelhecimento acelerado no grau de conversão de cimentos resinosos autoadesivos - Gallegos, Edison Xavier López (2019)
Indirect adhesive restorations are increasingly being part of the Oral rehabilitation procedures. With the purpose to reduce and minimize the difficulties and simplify the cementing technique with conventional adhesive resin cements, it was introduced a resin cement called self-adhesive for presenting chemical adhesion to dental tissues, ceramic and metal surfaces without the need for etching and adhesive systems applications. Some studies point out to the problems of degradation of cement during storage. The inhibitors and peroxides presented in the cement composition are organic chemical compounds and, therefore, are susceptible to degradation phenomena under storage. For all of these factors, the resin cements have limited storage period and changes in the mechanism of polymerization may occur during this period. The present study has been prepared containing some variables to research. The aim of this study was to investigate the consequences of different protocols and activation and accelerated aging of self-adhesive dual curing resin cements in the degree of conversion, as well as test the null hypothesis that the activation protocol of polymerization and the accelerated aging did not cause change in the degree of conversion the material tested. The activation protocol of polymerization and the accelerated aging caused significant changes in the degree of conversion of the materials tested.